Effects of awareness-raising approach versus input-flood treatment on collocation knowledge, writing profiency, and cognitive style among Iranian EFL learners - Mahvelati, Elaheh Hamed (2014)
The aim of this study was to explore the most viable way to enhance language learners’ knowledge of collocation and consequently improve their writing performance with regard to their individual cognitive style differences. More specifically, the effectiveness of implicit collocation instruction through the input-flood technique versus explicit collocation instruction through the awareness-raising approach was examined. Furthermore, the role of the learners’ cognitive style of field-dependence/independence (FD/FI) in benefiting from these two teaching methods was investigated. Three intact groups of learners, comprising 95 upper-intermediate adult learners, participated in this study. These groups were randomly assigned to the control and experimental groups. During the treatment period, each group was exposed to the same language input and the same course materials (except for the materials used to teach collocations in the experimental groups). The data were collected through both quantitative and qualitative methods. More specifically, the effects of the treatments were examined and compared quantitatively through writing and collocation pre-tests, immediate post-tests and delayed-post-tests. Then to shed more lights on the impacts of the treatments on the learners’ collocation learning and writing proficiency, semi-structured interviews were conducted with a group of FD and FI participants and also with the raters of the writing tests. In the case of the input-flood group, in addition to the interviews, the retrospective-reflective tasks and tests of intake were also administered to help the researcher gain clearer insight into the thought and attentional processes of the learners. The analysis of both quantitative and qualitative data revealed that the collocation awareness-raising approach was significantly superior to the implicit method of input flood treatment since it not only increased the FD and FI learners’ knowledge about the collocational fields of words but also helped them to use this knowledge in their English written production which consequently improved their writing performance. In addition, this method heightened their collocation awareness which consequently motivated them to put more efforts into learning more collocations. Moreover, the results showed that the FD and FI learners equally benefited from this type of treatment. The input-flood method was found to be beneficial for only the learners with FI tendencies. However, it is important to note that this method could only increase the FI learners’ passive knowledge about the collocational fields of the words but it could not encourage these learners to actively use them in their written output. In fact, it was found that this implicit instructional method was not successful enough to help them understand the concept of collocation. Thus, their writing performance was not improved as a result of this treatment. Based on the findings of the study, the collocation awareness-raising model proposed by Ying and Hendricks (2003) is modified by adding the step of L1-L2 contrastive analysis. Pedagogical implications for language educators and learners are provided as well.